Temperature Decreasing Circulation of Solar Panels Using Water Flow - Rosita Efriyanti; Ahmad Taqwa; Fatahul Arifin (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
This study aims to provide a clear picture of the efficiency of using solar panels as an alternative energy source compared to conventional energy, as well as to keep the temperature of the solar panels stable. Where the solar panel itself has a maximum body and temperature that affects the results of the solar panel. Solar panels experience a decrease in their ability to generate electricity when they overheat or exceed their effectiveness limits. Therefore, seeing the effectiveness of solar panels working at a temperature of 25 degrees Celsius, there is a desire to take advantage of the excess heat generated from solar panels by cooling the solar panels by flowing water through a capillary tube. Where the experimental results can be seen in the graph of solar panels that have not used cooling. showed a decrease in the absorption of solar panels, precisely at 11.30 am and had a voltage of 20.2V with a temperature of 3.1℃. shows a decrease in the power produced on the day of the study where at 11.30 am there was a decrease in power to the voltage from 20.4V to 19.00 V and it can be said that this was caused by an increase in temperature in three days which was also influenced by the heat earlier.